2019
DOI: 10.3389/fchem.2019.00095
|View full text |Cite
|
Sign up to set email alerts
|

Green Protocols in Heterocycle Syntheses via 1,3-Dipolar Cycloadditions

Abstract: The aim of this review is to provide an overview of green protocols for the organic synthesis of heterocycles via 1,3-dipolar cycloaddition. Particular attention has been devoted to the use of green solvents; reactions performed in ionic liquids, fluorinated solvents and water have been included. Also explored are several protocols that make use of catalyst-free reaction conditions, the use of microwave irradiation and activation by light exposure. Improvements over commonly used organic solvents will be under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 57 publications
(57 reference statements)
0
29
0
Order By: Relevance
“…The pair of diastereomer 5c were separated using the HPLC technique qualitatively. The mechanism of epoxidation includes a concerted reaction mechanism characterized by a four‐part, cyclic transition state, as a result, the electropositive, oxygen atom ended up in the cyclopropane ring, and the COO 2 H group becomes COOH . MMPP has electropositive oxygen atom on carboxylic group.…”
Section: Resultsmentioning
confidence: 99%
“…The pair of diastereomer 5c were separated using the HPLC technique qualitatively. The mechanism of epoxidation includes a concerted reaction mechanism characterized by a four‐part, cyclic transition state, as a result, the electropositive, oxygen atom ended up in the cyclopropane ring, and the COO 2 H group becomes COOH . MMPP has electropositive oxygen atom on carboxylic group.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies of pericyclic cycloadditions showed great benefits when insoluble reagents were suspended in water, explicating this effect due to a reaction rate acceleration for the "on water" conditions [65]. In particular, comparative studies of 1,3-dipolar cycloadditions in organic solvents with water as a co-solvent or only in pure water showed a remarkable rate acceleration increase, probably due to hydrophobic effects with organic reagents, a lowering of activation energy by hydrogen bonds in the transition state, and an increased solvation stabilization [66].…”
Section: 3-dc In Watermentioning
confidence: 99%
“…The objective of this report is the consideration of the use of some of these “unconventional” techniques in the 1.3‐DCs of NOs, giving coverage on the more significant progress made on the topic especially during the last ten years until February 2020. The following subjects have been considered: (a) the use of ILs and scCO 2 as alternative solvents in 1,3 DCs of NOs; (b) MW and US activation in NOs CAs; (c) NOs CAs under continuous flow …”
Section: Introduction and Objectivesmentioning
confidence: 99%